Study of the relative frequency of spontaneous pneumothorax recurrence with two policy therapies: A clinical trial - Gholamreza Mohajeri; Hamid Talebzadeh; Ali Fallah-Mehrjardi; Hamidreza Soltani; Mahdi Neshan (Advanced Biomedical Research, 2023)
Background: Spontaneous pneumothorax is a potentially fatal condition with a high risk of recurrence. The purpose of this study is to compare two different approaches to SP management. In the first group, patients underwent only chemical pleurodesis; in the second group, CT-scan, VATS, and then chemical pleurodesis was performed. Materials and Methods: This study is a non-randomized clinical trial conducted on 65 patients admitted to Al-Zahra Hospital in Isfahan with a primary complaint of sudden dyspnea and a definitive diagnosis of spontaneous pneumothorax. Two studies compared the main outcomes of recurrence within six months and the time until recurrence. Results: Age, sex, and BMI were matched between the two study groups. The side of the pneumothorax, smoking history, and pulmonary disease history did not differ significantly (P > 0.05). Pneumothorax recurrence did not differ significantly between the two groups (P: 0.477). Conclusion: This study demonstrated no distinction between VATS and chemical pleurodesis when using only chemical pleurodesis. However, because numerous studies have suggested that one of these techniques may be beneficial for patients with SP, it is recommended to conduct additional randomized controlled trials (RCTs) with a more detailed plan and more comparable procedures, although it appears that meta-analysis design may be effective given the abundance of available RCT studies.